Safety and immunogenicity of freeze-dried human rabies vaccines: A phase 3 clinical trial of Zagreb and Essen regimes - Jia Li; Zhiang Wu; Xiaohong Wu; Yunpeng Wang; Leitai Shi; Danhua Zhao; Haiyan Liang; Zhaojun Mo; Shouchun Cao (Human Vaccines & Immunotherapeutics)
Recently optimized freeze-dried rabies vaccines (Vero cell) are promising for rabies prevention; however, comparisons of Essen 5-dose and Zagreb 4-dose regimens are needed for clinical applications. This phase III clinical trial aimed to assess the safety and immunogenicity of candidate freeze-dried rabies vaccines developed for human use by Shandong Yeedo Biotechnology (Registration No.: CTR20182016, http://www.chinadrugtrials.org.cn/index.html). In total, 40 participants in stage I and 1797 subjects in stage II with an age range of 10–60 years were recruited. Both 4-dose and 5-dose experimental vaccines were well-tolerated in stage 1, with similar overall adverse event (AE) rates. In stage 2, systemic fever (35.39%) and local pain (48.91%) were common, and the rate of Grade 3 AEs was approximately 2.5%. Rates of local reactions and unsolicited AEs differed among groups (p = .045 and 0.011). Immunogenicity analyses showed higher antibody levels, seroconversion rates, and pre-immune seroconversion rates in the 4-dose experimental group versus the 5-dose group (p < .001) on day 7 post-first dose, with similar GMCs (geometric mean concentrations) by day 14. Pre-immune negative subjects had comparable antibody levels in the 4-dose and 5-dose experimental groups, outperforming the 5-dose control group (p = .039). The rate difference (95% CI) for first-dose seroconversion at 14 days post-vaccination among pre-immune antibody-negative subjects indicated non-inferiority between the 5-dose experimental and control groups. Overall, the Shandong Yeedo rabies vaccine demonstrated satisfactory safety and efficacy, offering a new option for rabies prevention.